Memory Politics in Contemporary Russia Television, Cinema and the State - Wijermars, Mariëlle (Taylor & Francis, 2018)
This book critically examines the role of cinema and television in shaping and spreading narratives of memory politics in contemporary Russia to provide a better understanding both of the various ways the Russian government practices memory politics, and the existence of alternative and critical voices and criticism.